Spontaneous Atrial Thrombosis in Aged Syrian Hamsters - McMartin, Donald N. (Thrombosis and Haemostasis, 1977)
Many of the aging Syrian hamsters maintained in our Division spontaneously develop atrial thrombosis accompanied by a consumption coagulopathy. The 50% mortality level is reached earlier by females (16 months) than by males (24 months). The incidence of thrombosis increases with age, beginning at 13.5 months in females and at 21.5 months in males, and the overall incidence (73%) is nearly the same for both sexes. Bilateral ventricular hypertrophy was found in thrombosed hearts. The hearts of most aged hamsters, whether thrombosed or not, had myxoid valvular thickenings and myocardial degeneration. Myodystrophic changes included hypertrophied nuclei, cytoplasmic vacuolation, fiber atrophy, and finally replacement fibrosis. Thrombosis probably resulted from local blood stasis secondary to cardiac failure. These hamsters may be an especially useful model for comparative study of the effects of aging and myocardial degeneration on spontaneous thrombosis.